Golden Generation 2045 Curriculum: Integrating Islamic Value, Digital Competence, and Reproductive Health To Address Indonesia’s Demographic Bonus - Mukhsin, Mukhsin; Alfani, Ilzam Hubby Dzikrillah (Fahmina: Jurnal Pendidikan Islam, 2025)
Indonesia is currently experiencing a demographic bonus period, presenting both a golden opportunity and a significant challenge on the path towards Golden Indonesia 2045. However, low digital competence, moral degradation, and adolescent reproductive health issues threaten the realization of a superior generation. This study aims to formulate an integrative 'Generation 2045' Curriculum Model that unites three main pillars: Islamic values, digital competence, and reproductive health. Employing a holistic curriculum integration framework grounded in the Maqasid al-Shari'ah (Objectives of Islamic Law) and 21st Century Skills paradigms, this research utilizes a qualitative literature study method with content analysis. The study produces a curriculum model that positions Islamic values as the philosophical-ethical foundation, digital competence as the tool, and reproductive health as the well-being guarantor. This model is operationalized through thematic integration, pedagogical approaches such as project-based learning, and implementation at the levels of school operational curriculum, extracurricular activities, and community engagement. Its implementation anticipates key challenges including teacher readiness in interdisciplinary teaching, the need for policy alignment within the Merdeka Curriculum framework, and disparities in digital infrastructure. The findings indicate that integrating these three pillars creates a mutually reinforcing synergy, is culturally relevant, and offers a holistic preventive approach. This model is proposed as an educational strategy to ensure the demographic bonus can be optimally utilized to realize a Golden Generation 2045. Furthermore, it calls for empirical research and development (RD) cycles for model validation and field testing.